Construction Know How from Northern Ireland : Ten Northern Ireland-based construction companies making a name for themselves in the Gulf.: Ten Northern Ireland-based construction companies making a name for themselves in the Gulf. (2016) - Invest Northern Ireland (Organization),
No abstract available